2019
DOI: 10.1111/cas.14208
|View full text |Cite
|
Sign up to set email alerts
|

Novel human Ab against vascular endothelial growth factor receptor 2 shows therapeutic potential for leukemia and prostate cancer

Abstract: Vascular endothelial growth factor receptor 2 (VEGFR2) is highly expressed in tumorassociated endothelial cells, where it modulates tumor-promoting angiogenesis, and it is also found on the surface of tumor cells. Currently, there are no Ab therapeutics targeting VEGFR2 approved for the treatment of prostate cancer or leukemia.Therefore, development of novel efficacious anti-VEGFR2 Abs will benefit cancer patients. We used the Institute of Cellular and Organismic Biology human Ab library and affinity maturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Further possible treatment options, including direct targeting of VEGFR-2-expression, indirect inhibition of angiogenesis, and targeting the interplay between tumor or stromal cells and angiogenesis, have been evaluated. Lu et al suggested that anti-VEGFR-2-AF is a prospective therapeutic Ab for prostate cancer treatment that inhibits angiogenesis, through vascular endothelial cells, and tumorigenesis at the same time by VEGFR-2-expressing tumor cells [ 118 ]. The therapeutic efficacy of anti-VEGFR-2-AF is currently under study in preclinical trials using solid and liquid xenograft mouse models [ 118 ].…”
Section: Anti-angiogenic Therapy In the Most Common Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Further possible treatment options, including direct targeting of VEGFR-2-expression, indirect inhibition of angiogenesis, and targeting the interplay between tumor or stromal cells and angiogenesis, have been evaluated. Lu et al suggested that anti-VEGFR-2-AF is a prospective therapeutic Ab for prostate cancer treatment that inhibits angiogenesis, through vascular endothelial cells, and tumorigenesis at the same time by VEGFR-2-expressing tumor cells [ 118 ]. The therapeutic efficacy of anti-VEGFR-2-AF is currently under study in preclinical trials using solid and liquid xenograft mouse models [ 118 ].…”
Section: Anti-angiogenic Therapy In the Most Common Cancersmentioning
confidence: 99%
“…Lu et al suggested that anti-VEGFR-2-AF is a prospective therapeutic Ab for prostate cancer treatment that inhibits angiogenesis, through vascular endothelial cells, and tumorigenesis at the same time by VEGFR-2-expressing tumor cells [118]. The therapeutic efficacy of anti-VEGFR-2-AF is currently under study in preclinical trials using solid and liquid xenograft mouse models [118].…”
Section: Prostate Cancermentioning
confidence: 99%
“…This finding will aid in future investigations on the development of reliable and effective antiangiogenic therapeutic options for canine PC, similar to the scenario already delineated in human PC. In human PC, the mechanism of angiogenesis 29–31 as well as the association between tumor hypoxia and vasculogenesis have been widely studied 31 . Therefore, different therapeutic strategies have been developed to target the angiogenic markers, including the anti‐VEGFR‐2 monoclonal antibodies 29 and oncolytic vaccines expressing anti‐VEGF antibodies 32 …”
Section: Discussionmentioning
confidence: 99%
“…In human PC, the mechanism of angiogenesis 29–31 as well as the association between tumor hypoxia and vasculogenesis have been widely studied 31 . Therefore, different therapeutic strategies have been developed to target the angiogenic markers, including the anti‐VEGFR‐2 monoclonal antibodies 29 and oncolytic vaccines expressing anti‐VEGF antibodies 32 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, development of an excellent anticancer agents are very much essential, especially ones with potent biological activities, enzyme inhibitory activities and low/no toxicity [2][3][4][5] (Figure 1). Regarding enzyme inhibitory activities: (i) cyclin-dependent kinases (CDKs) are considered as a vital feature, inciting various key transitions in the cell cycle for cancer cells, in addition to instructing apoptosis, transcription and exocytosis; (ii) the epidermal growth factor receptor (EGFR) [6] kinase enzyme promote overexpression, and overexpression of certain proteins may play a role in various cancer development [7][8][9][10][11][12][13][14][15]; (iii) the vascular endothelial growth factor receptor 2 (VEGFR-2) [16,17] is highly expressed in tumor-associated endothelial cells, where it modulates tumor-promoting angiogenesis, and it is also found on the surface of tumor cells [18]; (iv) FMS-like tyrosine kinase-3 (FLT-3) is a protein found in humans and is encoded by the FLT-3 gene [19][20][21]. Mutations of the FLT-3 receptor can lead to the development of leukemia, a cancer of bone marrow hematopoietic progenitors [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%